Pengambilan Keputusan Konsumen Terhadap Pembelian pada Toko Bangunan Pintu Rizki - Fani Bahari; Yoga Putra Pratama; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
The development of today's business ventures requires consumers to be smart, careful, efficient and effective in choosing the desired product. With that attitude, consumers will not be disappointed with what products they have purchased. Requirements that must be met by a company to be successful in competition is trying to achieve goals by maintaining and increasing customers. Pintu Rizki Building Store is a business engaged in the retail sector of building materials, located on Jln. Gempol, Tanjungpura, Karawang. This business was founded in 2010 and currently has 8 employees. The activities carried out by this shop are providing and serving the needs of consumers in shopping for building materials. The method used in this article is observation, it aims to find out about consumer decision making in the context of purchasing at Pintu Rizki's building store. This observation also provides insight into the factors that influence consumer purchasing decisions in shopping at Pintu Rizki stores. The results of this article show that consumers tend to buy products that are of high quality and have affordable prices. In addition, consumers also consider factors such as store reputation, product availability, and services provided by the store.